High-performance work system on sustainable organizations performance in SMEs - Eniola, Anthony Abiodun; Kenzhin, Zhaxat; Chimwai, Ledwin; Kairliyeva, Gaukhar; Adeyeye, Mercy Modupe; Chidoko, Clainos; Mutsikiwa, Munyaradzi (Business: Theory and Practice, 2023)
Managing performance is quite easy, but sustaining that performance is the real challenge for organizations in the 21st century. Hence, the research’s main objective is to examine the impact of high-performance work system on sustainable organizational success in small and medium business (SMEs). Moreover, for global business organizations to succeed innovation must be involved. Therefore, the study is mediated by the Innovative work behaviour. Data were obtained among 820 SME employees in Nigeria. The Analysis used Partial Least Square (PLS) to check the hypothesis. In order to introduce creativity or inspire workers to behave innovatively in the workplace, they need a sense of well-being to actively engage employee organisations. This research will allow managers to agree to invest in workers so that employees work successfully and display creative actions in order to achieve sustainable organisation. This study adds to the scientific management literature by exploring the phenomena sustainable lens innovation and high-performance work by the SMEs in concurrently improve innovation-specific skills, inspiration, and voice habits across employees, resulting in higher innovation efficiency.